2022
DOI: 10.3390/ph15101278
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of HDL’s to piHDL’s Proteome in Patients with Chronic Inflammatory Diseases, and HDL-Targeted Therapies

Abstract: Chronic inflammatory diseases, such as rheumatoid arthritis, steatohepatitis, periodontitis, chronic kidney disease, and others are associated with an increased risk of atherosclerotic cardiovascular disease, which persists even after accounting for traditional cardiac risk factors. The common factor linking these diseases to accelerated atherosclerosis is chronic systemic low-grade inflammation triggering changes in lipoprotein structure and metabolism. HDL, an independent marker of cardiovascular risk, is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 595 publications
0
16
0
Order By: Relevance
“…Both SAA1 and APOA4 play an important role in inflammation and the acute phase response. 51,52 As mentioned above, SAA1 has been consistently found in HDL from individuals with high cardiovascular risk and has been associated with loss of anti-inflammatory function. 53 The presence of SAA in HDL reduces their affinity for hepatocytes but increases their binding affinity to macrophages.…”
Section: Discussionmentioning
confidence: 91%
“…Both SAA1 and APOA4 play an important role in inflammation and the acute phase response. 51,52 As mentioned above, SAA1 has been consistently found in HDL from individuals with high cardiovascular risk and has been associated with loss of anti-inflammatory function. 53 The presence of SAA in HDL reduces their affinity for hepatocytes but increases their binding affinity to macrophages.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, HDL increases the clearance of LPS via SR‐B1, which acts as an LPS‐binding protein 41 . Therefore, low HDL is negatively correlated with sepsis and augments systemic inflammatory reactions as HDL‐SR‐B1 acts as direct anti‐inflammatory agent‐driven cholesterol for glucocorticoid synthesis 62,63 . Van‐Leeuwen and colleagues observed that HDL serum levels rapidly declined in patients with severe sepsis, 64 suggesting a protective role of HDL against bacterial sepsis.…”
Section: Main Textmentioning
confidence: 99%
“…41 Therefore, low HDL is negatively correlated with sepsis and augments systemic inflammatory reactions as HDL-SR-B1 acts as direct anti-inflammatory agent-driven cholesterol for glucocorticoid synthesis. 62,63 Van-Leeuwen and colleagues observed that HDL serum levels rapidly declined in patients with severe sepsis, 64 suggesting a protective role of HDL against bacterial sepsis. Furthermore, it was observed that administration of reconstituted HDL can attenuate LPS-induced inflammation 64 proposed that HDL could be a valuable therapeutic approach for sepsis.…”
Section: Dysfunctional Hdl In Infections and Immune Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The alteration of HDL structure and function in disease is both an important biomarker of the diseased state as well as a potential critical factor influencing disease progression and regression [ 145 , 146 ]. Many post-translational modifications associated with inflammatory diseases render HDL-associated components dysfunctional and hence disrupt its normal functionality [ 147 ]. Figure 2 summarizes the modifications of selected HDL constituents in cardiovascular disease pathophysiology, highlighting its importance as a cause (therapeutic target) or consequence (diagnostic biomarker) of the disease.…”
Section: Hdl Particles Are Remodeled In Cardiovascular Disease and Lo...mentioning
confidence: 99%